Renal Clearance of B-Type Natriuretic Peptide and Amino Terminal Pro-B-Type Natriuretic Peptide : A Mechanistic Study in Hypertensive Subjects - VAN KIMMENADE, Roland R. J; JANUZZI, James L; BAKKER, Jaap A; HOUBEN, Alphonse J; RENNENBERG, Roger; KROON, Abraham A; CRIJNS, Harry J. G. M; VAN DIEIJEN-VISSER, Marja P; DE LEEUW, Peter W; PINTO, Yigal M (Journal of the American College of Cardiology, 2009)
This study sought to compare the renal clearance mechanisms of B-type natriuretic peptide (BNP) and amino terminal pro-B-type natriuretic peptide (NT-proBNP). The small molecular weight proteins (SMWPs) BNP and NT-proBNP both inversely correlate with glomerular filtration rate (GFR). Whether this association is causal or confounding is unknown and has been the basis of widespread speculation. We combined measurements of BNP and NT-proBNP concentrations in the renal arteries and veins of 165 subjects undergoing renal arteriography with invasive renal plasma flow (RPF) measurements and echocardiography. Fractional extraction (FE) of BNP and NT-proBNP was computed. The BNP and NT-proBNP concentrations correlated similarly to GFR (r = -0.35 and r = -0.30, respectively; p < 0.001 for both) but the NT-proBNP/BNP serum ratio was negatively associated with GFR (r = -0.21, p = 0.008). Median FE(BNP) was 0.21 (interquartile range [IQR] 0.16 to 0.22) for left and 0.22 (IQR 0.17 to 0.29) for right kidneys. Median FE(NT-proBNP) was 0.16 (IQR 0.09 to 20) for left and 0.18 (IQR 0.12 to 0.22) for right kidneys. The FE(BNP) correlated with GFR (left: r = 0.26, p = 0.008; right: r = 0.21, p = 0.03) as did FE(NT-proBNP) (left: r = 0.25, p = 0.005; right: r = 0.20, p = 0.02). Although FE(BNP) and FE(NT-proBNP) correlated strongly with each other (left: r = 0.66; right: r = 0.60; p < 0.001 for both), left and right FE(NT-proBNP/BNP) ratios were not influenced by GFR (r = 0.10, p = 0.30 and r = 0.08, p = 0.43, respectively). Multivariate analyses confirmed that FE was not independently associated with BNP or NT-proBNP concentrations. Contrary to widespread belief (but in line with the renal physiology of SMWP), BNP and NT-proBNP are equally dependent on renal function for their clearance.